Influence of particle fragmentation and non-sphericity on the determination of diffusive and kinetic fluidized bed biochar combustion data (Fuel, 2014)
In several studies of batch combustion of mineral or vegetal coal in fluidized bed reactors, it is assumed that the fragmentation of the fuel particles is meaningless and also that these particles are spheres. None of these assumptions is corrected although they are commonly accepted in many design and calculation procedures. Here the influence of the above mentioned phenomena on the experimentally obtained diffusive and kinetic data are compared with the equivalent results previously obtained by ignoring such occurrences. Four chars made from typical woods from the Portuguese forest were tested. The results show that for the studied chars, ignoring the phenomenon of fragmentation, diffusive and kinetic data are overestimated by about 5–10%, whereas not taking into account the actual shape of the particles overestimates the diffusive data between 45% and 50% and the kinetic data between 25% and 30%. This highlights the extreme importance of particle shape in the study and modeling of char combustion in fluidized bed reactors.